Pollinator effectiveness and pollination dependency of bilberry (Vaccinium myrtillus) in Swedish hemi-boreal forests - Bartholomée, Océane; Björnberg, Jacob; Smith, Henrik G.; Kendall, Liam (Journal of Pollination Ecology, 2024)
Intensification of forest management to increase production of biomass has resulted in considerable habitat degradation with negative impacts on insect biodiversity, including beneficial insect groups such as pollinators. Yet, little is known about how reliant forest understory plants, such as bilberry (Vaccinium myrtillus), are on insect pollinators for reproduction. Here, we quantified the structure of the bilberry flower visitor community, compared the pollination effectiveness of the most common pollinators, and experimentally quantified bilberry pollination dependency. The bilberry pollinator community was comprised of several bee and hoverfly taxa. Bumblebees were the most important pollinators due to their high abundance and pollination effectiveness. Other bees, in particular, Andrena spp., and to a smaller extent, hoverflies, were also effective pollinators. Furthermore, bilberry was strongly pollen-limited, with only 40% of open-pollinated flowers setting fruit. Bilberry supports a diverse flower visitor community within hemi-boreal forests, for which it is highly dependent for reproduction. Given the ecological and cultural value of bilberry, the importance of insect pollinators for understory plants should be considered within forest management strategies.